Caldera Toba UGG Yellow Card and Stakeholder Synergy Issues - Bahar, Alifia (Journal La Sociale, 2025)
The designation of the Caldera Toba as a UNESCO Global Geopark (UGG) opens up great opportunities for Indonesia to be increasingly recognized in the eyes of the world, especially in the field of tourism. The uniqueness of the Caldera's geographical and morphological conditions is enhanced by the development and construction to promote the caldera to foreign and local tourists. However, in 2023 due to the lack of synergy between the government and local communities, UNESCO gave a yellow card as a warning to the Caldera Toba UGG. This research will argue the problems that occur in the Caldera Toba UGG and offer solutions that can be discussed again by the parties. The method used in this research is a literature study using books, reports, articles, journals, and other literature sources relevant to this discussion. Ecological damage caused by external and internal factors is the main factor in the damage and decline in tourist visits, in addition to the segmentation of power between stakeholders. These two factors are interrelated and need a balance of roles to overcome the problems of the Caldera Toba UGG yellow card.